New methods in diagnosis and therapyExpanded indications for transcatheter renal denervation - Fronczak, Aneta; Jasińska, Anna; Biernacka, Elżbieta Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Renal denervation (RDN) is a catheter-based procedure introduced in 2009 as a treatment of resistant hypertension. The method is based on the concept that resistant hypertension is a result of hyperactivity of the sympathetic nervous system (SNS), and therefore reducing the impact of the SNS by ablating the renal nerves should eliminate the condition. Since 2009 numerous investigators have proven the procedure to be safe and effective, which contributed to the quick success and wide spread of the method, subsequently triggering further research in this area. The dynamic distribution of the procedure induced investigators to examine the influence of RDN on other conditions involving hyperactivity of the SNS (such as atrial fibrillation or ventricular arrhythmia). A few studies aiming to explain the influence of RDN on arrhythmias in patients with resistant hypertension have been conducted. The results in treating atrial fibrillation additionally to pulmonary vein ablation and electrical storm appear to be promising; however, the data are limited and further investigations needs to be done. The influence of RDN on insulin resistance, left ventricular hypertrophy and heart failure are possible. Perspectives of expanding indications are discussed. Renal denervation appears to be a promising way of treating hypertension and raises hope for a wider group of patients with conditions closely related to hyperactivity of the sympathetic nervous system such as arrhythmia.